Parents' perceptions of tele-audiological testing in a rural hearing screening program in South India. (October 2016) - Ramkumar, Vidya; Selvakumar, K.; Vanaja, C.S.; Hall, James W.; Nagarajan, Roopa; Neethi, J.
Abstract: Introduction: Tele-diagnostic audiological testing in a hearing screening program for infants and young children is a novel practice, and this study is the first to explore its application in a rural community. It is important to understand parental perceptions and confidence when introducing a new process such as tele-audiological diagnostic testing in rural areas. Method: A questionnaire with 17 rater-administered items was designed to elicit comments concerning the quality of tele-hearing testing and video-conferencing, access to tele-hearing testing, and parents' attitudes regarding tele-hearing testing in the village. The questionnaire was administered by an audiologist not involved in tele-diagnostic testing to avoid bias. Results: Parents perceived tele-hearing testing as equal in quality to in-person testing. Technical factors such as good video-conferencing quality and logistical factors such as ease of access due to reasonable travel time to testing facility could have influenced these perceptions. Conclusions: While these results show tele-hearing testing is an acceptable alternative, occasional poor signal quality should be addressed prior to large-scale implementation.